Comparative Analysis of State Universities on Website Performance in Aceh Using the PIECES Method - Suhaili Sahibul Muna; Nurdin Nurdin; Taufiq Taufiq (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2023)
Technological developments have had a rapid impact on the CIVITAS Academic environment, especially in Aceh. The website has become a major requirement for state universities (PTN) as a fast, actual and reliable information distribution medium in supporting lecture activities in the Digital Era 4.0. The purpose of this study was to obtain results from the PIECES method test on the website in terms of its effectiveness as an information distribution medium. Therefore, the presence of website performance analysis research using the PIECES method is very important in measuring website effectiveness. PIECES uses the variables Performance, Information, Economics, Control, Efficiency, and Service. The importance of this research is to provide information in analyzing the use of websites at universities (PTN) in Aceh, as well as analyzing the strengths and weaknesses of each website. The research step begins with the distribution of questionnaires on the variables Information, Economics, Efficiency, and Service responded to by respondents online. Then perform a website performance analysis using Google Page Speed Insight (GPSI) and GTMetrix online tools. In variable control, use Qualys SSL Lab and SECURi. The results showed USK Information with a value of 4.26, Economic 4.13, Efficiency 4.4, and Service 4.36. UINAR obtained 4.26 in the subject Information, Economic 4.13, Efficiency 4.3, and Service 4.36. UNIMAL obtained Information 4.26, Economic 4.23, Efficiency 4.3, and Service 4.15. UNSAM with the Information subject obtained 4.1, Economic 4.13, Efficiency 4.19 and Service 4.15 and UTU Information subject 4.24, Economic subject 4, Efficiency 4.19 and Service with a value of 4.21. The GPSI and GTMetrix tests showed significant results with the highest score of 97 UNSAM on GPSI. Results from Qualys SSL Lab and SCURi, all websites are safe to access.